Effect of Accounting Information Systems and Internal Control Systems on the Quality of Financial Reporting with Organizational Commitment as Moderating Variables at PT Mopoli Raya - Syahmina Hamimi; Irfan Irfan; Widia Astuty (Budapest International Research and Critics University, 2021)
This study aims to determine and analyze effect of accounting information systems and internal control systems on the quality of financial reporting with organizational commitment as moderating variables at PT Mopoli Raya. This research method uses quantitative associative. The object of the research was PT Mopoli Raya with a total population of 45 people, all of whom were used as research respondents. The data analysis used a structural equation modeling-partial least square (SEM-PLS) approach. The results of the study found that the accounting information systems effect on the quality of financial reporting. Internal control systems effect on the quality of financial reporting. Organizational commitment moderates effect of accounting information systems on the quality of financial reporting. Organizational commitment moderates effect of internal control systems on the quality of financial reporting.